2012
DOI: 10.1103/physrevd.86.095028
|View full text |Cite
|
Sign up to set email alerts
|

Higgs boson production and decay: Effects from light third generation and vectorlike matter

Abstract: We study the implications of light third generation sparticles on the production cross section and decay widths of a light CP-even Higgs boson. For simplicity, we consider scenarios in which only one of the sfermions from the third generation is light. For each case, we attempt to explain the apparently large enhancement in the Higgs production and decay in the diphoton channel with small deviations in the ZZ channel. In the MSSM framework we find that only a light stau can explain these observations while kee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 97 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…On the other hand, CMS collaboration reported a best-fit signal strength in their main analysis [4] where, µ γγ = 1.14 +0. 26 −0. 23 .…”
Section: Jhep02(2015)124mentioning
confidence: 99%
“…On the other hand, CMS collaboration reported a best-fit signal strength in their main analysis [4] where, µ γγ = 1.14 +0. 26 −0. 23 .…”
Section: Jhep02(2015)124mentioning
confidence: 99%
“…(For some vectorlike fermion extension examples, see Refs. [4][5][6][7][8][9][10][11][12][13][14][15].) Certainly, detailed analyses of these extensions are worthwhile and might provide guidance to experimenters searching for physics beyond the SM.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients in front of D are fixed by charges under the broken U(1). It has been shown that for D > 0, m 10 > m 16 and universal other soft terms proper REWSB is consistent with top-bottom-tau Yukawa unification [48]. The crucial role in top-bottom-tau Yukawa unification is played by the sign of µ because it controls the sign of the dominant finite SUSY threshold corrections to the bottom mass [40,41,74]:…”
Section: Top-bottom-tau Yukawa Unification and Rewsbmentioning
confidence: 96%
“…refs. [15][16][17][18][19][20][21][22][23][24][25][26][27]. In this paper we focus on the possibility that such new states are supersymmetric and study enhanced h → γγ rate in the MSSM.…”
Section: Jhep10(2013)088mentioning
confidence: 99%